CHARACTERISTICS ANALYSIS OF ADSORBENT FROM RUBBER TREE TRUNK AND RUBBER SEED SHELLS - Desi Nurandini; Riani Ayu Lestari; Muhammad Zeva Prayitno; Isna Syauqiah (Universitas Lambung Mangkurat, 2022)
The efforts to control heavy metal waste are developingg to obtain an economical, effective, and efficient method. One method that is widely used in industry is adsorption. In general, the use of conventional adsorbents requires relatively more expensive operational and regeneration costs, thus it is necessary to investigate alternative adsorbents derived from nature. Local commodities that can be taken as the basic material for adsorbents are rubber plants. In the rubber seed shell there are fibers containing cellulose, hemicellulose, lignin, and waxes. The rubber tree trunk at the base has a relatively high cellulose content (67.38%), the middle part has a cellulose content of (59.37%) and the end part has a cellulose content of (45.73%). Therefore, this study was conducted to determine the potential of rubber stems and rubber seed shell waste to be processed into adsorbents. The making of the adsorbent is preceded by the delignification stage and then followed by the activation process. Based on the characterization tests that have been carried out, it is known that the moisture content in the biosorbent of the rubber seed and shell is 10% and 11%, while the ash content is 1.23% and 2.33%, respectively. The volatile matter levels for the adsorbents from the stems and shells were 6.43% and 6.18%, respectively.The efforts to control heavy metal waste are developingg to obtain an economical, effective, and efficient method. One method that is widely used in industry is adsorption. In general, the use of conventional adsorbents requires relatively more expensive operational and regeneration costs, thus it is necessary to investigate alternative adsorbents derived from nature. Local commodities that can be taken as the basic material for adsorbents are rubber plants. In the rubber seed shell there are fibers containing cellulose, hemicellulose, lignin, and waxes. The rubber tree trunk at the base has a relatively high cellulose content (67.38%), the middle part has a cellulose content of (59.37%) and the end part has a cellulose content of (45.73%). Therefore, this study was conducted to determine the potential of rubber stems and rubber seed shell waste to be processed into adsorbents. The making of the adsorbent is preceded by the delignification stage and then followed by the activation process. Based on the characterization tests that have been carried out, it is known that the moisture content in the biosorbent of the rubber seed and shell is 10% and 11%, while the ash content is 1.23% and 2.33%, respectively. The volatile matter levels for the adsorbents from the stems and shells were 6.43% and 6.18%, respectively.